EFFECT OF BOARD GENDER DIVERSITY ON THE PERFORMANCE OF COMMERCIAL BANKS IN KENYA - Ekadah John Wachudi; Josphat Mboya (European Scientific Journal, ESJ, 2012)
The purpose of this paper was to analyze the effect of board gender diversityon performance of commercial banks in Kenya for the period 1998-2009. Stepwise regression was used to analyze the effect of board diversity on performance. It was found that boards of commercial banks in Kenya are male-dominated. On average, out of a typical board size of 8 members, only 1 is a female director. Finally, this study finds that board diversity has no effect on performance of banks in Kenya.